Acculturation and Anger Expression Among Iranian Migrants in Germany - Gilan, Donya; Werner, Antonia M.; Hahad, Omar; Lieb, Klaus; Frankenberg, Emily; Bongard, Stephan (Frontiers in Psychology, 2022)
Cultural and biographical influences on the expression of emotions manifest themselves in so-called “display rules”. These rules determine the time, intensity, and situations in which an emotion is expressed. To date, there is only a small number of empirical studies available, which deal with the transformation of display rules for emotions. In this study, this transition is examined as part of a complex acculturation process among Iranian migrants for the emotion of “anger”. In the cross-sectional study, Germans (n=61), Iranians (n=61), and Iranian migrants in Germany (n=60), who are differentiated according to their acculturation strategy (assimilation, separation, integration, marginalization), using the Frankfurt Acculturation Scale (FRACC), were assessed regarding their anger expression behavior. To measure anger expression, a questionnaire developed in a preliminary study was used, which measures anger intensity and anger expression based on responses to 16 vignettes. Multivariate analyses of variance (MANOVA) were conducted, which shows that Iranians and Iranian Migrants reported higher anger ratings than Germans. Further findings suggest that transformation processes may have affected Iranian migrants in terms of their expression of anger. This is particularly the case for suppressed anger (anger-in). Thus, people with a higher orientation towards the receiving culture reported on average lower anger-in. These results suggest that there is different emotional expressive behavior among Iranian migrants, depending on their orientation towards the cultural norms and values of the heritage and the receiving culture. The results provide new insights into socio-cultural and individual adjustment processes.